Pengaruh Pajak, Ukuran Perusahaan, Profitabilitas, Dan Exchange Rate Terhadap Transfer Pricing - Muthia Adelia, Linda Santioso (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to find out and obtain empirical evidence about the effect of tax, firm size, profitability, and exchange rate on transfer pricing of the manufacturing companies listed in the Indonesia Stock Exchange in the period of 2016-2018. This research the samples used 68 samples of manufacturing companies have been selected using purposive sampling method. Data processed with SPSS version 23 using logistic regression analysis. Research data using financial statements accessed through the official website of the IDX www.idx.ac.id. The result of this research showed that tax has a significant negative effect on transfer pricing, while firm size, profitability, and exchange rate have no significant effect on transfer pricing.